DEVELOPMENT AND EMPOWERMENT OF HALAL MSMES TO ENHANCE COMPETITIVENESS IN ARGAMAKMUR CITY, NORTH BENGKULU DISTRICT - Pefriyadi, Pefriyadi; Alfansi, Lizar; Darta, Effed; Indriani, Reni (PT. Altin Riset Publishing, 2025)
The objective of this PKM activity is to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Argamakmur City, North Bengkulu Regency. The main focus is to provide a deep understanding of the importance of halal certification and to improve business management competencies following Sharia principles. This enables MSMEs to expand their market and boost consumer trust in their products. The methods employed include training and workshops, mentoring, as well as monitoring and evaluation. Training and workshops aim to provide knowledge on halal certification procedures, halal business management, and marketing strategies. Mentoring is conducted periodically to ensure the proper implementation of the knowledge provided. Monitoring and evaluation are carried out to measure progress and the effectiveness of the activities. The results show a significant increase in MSME actors' understanding and awareness of halal certification. Several MSMEs have successfully obtained halal certification and reported increased consumer trust and product sales. The Halal MSME Development and Empowerment Program has successfully achieved its goal of enhancing MSME competitiveness in Argamakmur City, North Bengkulu Regency. With halal certification and improved business management competencies, MSMEs are better prepared to face market competition and attract more consumers.